The Role of Ex-Industrial SMEs in Bringing Prosperous Economic Development for the Residents of Wedoro Village - Nurul Ayu Andari; Rolita Adelia Prasetya; Fransiscus Xaverius Sri Sadewo (TEMALI : Jurnal Pembangunan Sosial, 2022)
The problems experienced by SME actors often become obstacles in society to improve their economic business such as business licensing, limited capital, expansion in marketing, constraints during the production process, and management of financial management. This research uses a qualitative type with Parsons's AGIL theory. The aim is to find out the division of roles of recycling empowerment actors and to analyze the resilience of this community through AGIL analysis. The research location was chosen because the empowerment carried out through Ex-Industry SMEs was successful due to an equilibrium role distribution system. The research subjects were selected using a purposive method. Data was collected using two primary data types (observation and interviews) and secondary data (through digital libraries). The analysis used in this study is the AGIL scheme's structural functionalism analysis focusing on analyzing the roles of Ex-Industry SME actors and Wedoro Hamlet residents in carrying out economic activities. The data validity checking technique used is triangulation. This research shows that their adaptation is carried out by prioritizing products in terms of quality and expanding the market to be able to compete with Chinese-owned products, goal orientation is carried out through conducting market research, innovation and creativity, which are continuously updated to increase market turnover, the latency that is applied is the value of discipline and kinship to strengthen solidarity between employers and employees, and the integration that is built is to establish a sense of solidarity and employee welfare to maintain business continuity.